La situation des négociations relatives au mécanisme REDD: Points de consensus, options pour aller de l’avant et besoins en matière de recherche afin de soutenir le processus - Verchot, Louis V.; Petkova, E. (Center for International Forestry Research, 2010)
The United Nations Collaborative Programme on Reducing Emissions from Deforestation and Forest Degradation in Developing Countries (UN-REDD) commissioned this report from the Center for International Forestry Research (CIFOR) to summarize the current state of negotiations towards a decision in Copenhagen, specifically outlining areas of consensus, options for resolving areas where consensus has not yet been reached, and priorities for research to support successful implementation of an international REDD Programme following a decision at the 15th Conference of the Parties (COP) in Copenhagen.